Refleksi Budaya Lampau Leksikon Kebendaan Peribahasa Banjar: Kajian Etnolinguistik - Norvia Hanafi (Balai Bahasa Kalimatan Selatan, 2020)
Peribahasa Banjar merupakan salah satu jenis karya sastra lama yang masih pamiliar dikalangan etnik Banjar. Namun minimnya pengetahuan tentang leksikon kebendaan yang merefleksikan budaya lampau membuat sulitnya memahami maksud dan tujuan penggunaan leksikon kebendaan dalam peribahasa Banjar. Leksikon kebendaan budaya lampau merupakan kata benda yang tertuang dalam peribahasa Banjar yang dapat memberikan gambaran terhadap budaya (kebiasaan) etnik Banjar zaman dahulu atau masa yang sudah lampau. Penelitian ini bertujuan (1) mengkalsifikasikan leksikon kebendaan yang merepleksikan budaya lampau dalam peribahasa Banjar, (2) mendeskripsikan leksikon kebendaan yang merepleksikan budaya lampau dalam peribahasa Banjar. Peneitian ini menggunakan metode deskriptif kualitatif. Data berupa leksikon kebendaan budaya lampau dalam peribahasa Banjar. Data yang dikumpulkan bersumber dari studi pustaka. Hasil penelitian ini menunjukkan: (1) leksikon kebendaan yang merepleksikan budaya lampau dalam peribahasa Banjar meliputi: (a) benda yang digunakan di rumah, (b) benda yang digunakan di sungai, dan (b) benda yang digunakan untuk huma (bercocok tanam). (2) repleksi budaya lampau dalam peribahasa Banjar direalisasikan dalam bentuk kebendaan yang metaforis. Pemataforisan kebendaan ke dalam peribahasa Banjar merupakan wujud dari penggambaran budaya Banjar. Leksikon kebendaan dalam peribahasa Banjar adalah sebagian kecil dari kekayaan bahasa Banjar yang sarat dengan budaya lampau, budaya yang mulai ditinggalkan oleh masyarakat suku Banjar .Banjar proverb is one of the old literary works that are still familiar in Banjar ethnicity. However, the lack of knowledge about the material lexicon that reflects past culture makes it difficult to understand the purpose or the aim of using material lexicon in Banjar proverbs. The old culture material lexicon is a noun contained in Banjar proverb that can provide an overview of the ethnic culture (customs) of the ancient Banjar or the past. The purposes of this study are (1) to classify the material lexicon that reflects the past culture in Banjar proverb, (2) to describe the material lexicon that reflects the past culture in the Banjar proverb. This research uses a descriptive qualitative method. The data are in the form of a lexicon of past culture material in Banjar proverb. Data are collected from the literature study. The results of this study indicate: (1) material lexicons that reflect a past culture in Banjar proverb include: (a) the objects used at home, (b) the objects used in rivers, and (b) the objects used for farming. (2) cultural reflection of the past in Banjar proverb is realized in the form of metaphorical material. The use of a metaphor of material in Banjar proverb is a form of Banjar cultural depiction. The material lexicon in Banjar proverb is a small part of the wealth of Banjar language which full of past culture, a culture that has already left by Banjar ethnic.